Volunteering and Youth Development - Qing-Qing Lin; Julie Jie Wen (Selected Topics in Humanities and Social Sciences Vol. 7, 2021)
Volunteering contributes to youth development although the process of how changes occur in the youth has not been clearly defined. The research focuses on a volunteering case study, namely Mei Xian Team, where college students from urban universities spend time in rural China to help with teaching in the remote villages. From in-depth interviews, focus group, and observation, the research explores how the volunteering experience changing the attitude, behaviour, and socialisation. Young volunteers developed their personalities during their journey of helping rural children with limited resource. Youth development is enhanced in the volunteering process by interaction, conflict resolution, and socialisation. There were diverse modes of personal and interpersonal interactions among the research informants. These volunteer tourists manifested how their travel experience led to personal shifts and socialisation of youth travellers.